Diagnostic and therapeutic aproachto acute pancreatitis during pregnancy - Quiñonez-Corado, Josseline Stefany (2024)
Objective: To determine the current diagnostic and therapeutic approaches for managing acute pancreatitis in pregnancy. Material and methods: we conducted a comprehensive review of journal articles and textbooks focused in pregnancy and surgery published between 2012 and 2022. We utilized databases and search engines such as BVS, PubMed, Hinari, Medline, Scielo, Scholar Google, metasearch engines, UptoDate. The review included review articles, observational studies, case reports, meta-analyses and clinical practice guidelines, both in Spanish and English. The inclusion criteria were centered on studies involving pregnant women aged 18-40 with acute pancreatitis. Results: the physiological changes during pregnancy increase the predisposition to experience acute pancreatitis. The therapeutic approach must be individualized and multidisciplinary. Treatment strategies may vary based on the severity of the condition, stage of pregnancy, and underlying causes. Conclusion: recent advancements in the understanding of acute pancreatitis in pregnancy have led to a significant reduction in maternal-fetal mortality, reported to be less than 5%. Despite these improvements, there remains a lack of specific clinical guidelines tailored to the management of acute pancreatitis in pregnant women. Further research is needed to develop standardized treatment protocols that can optimize outcomes for both the mother and fetus.